Shoe collar height and heel counter-stiffness for shoe cushioning and joint stability in landing - Lam, W.-K.; Cheung, C. C.-W.; Leung, A. K.-L. (Journal of Sports Sciences, 2020)
This study examined the effects of shoe collar-height and counter-stiffness on ground reaction force (GRF), ankle and knee mechanics in landing. Eighteen university basketball players performed drop landing when wearing shoes in different collar height (high vs. low) and counter-stiffness (stiffer vs. less stiff). Biomechanical variables were measured with force platform and motion capturing systems. Two-way repeated measures ANOVA was performed with a = 0.05. Wearing high collar shoes exhibited smaller peak ankle dorsiflexion and total sagittal RoM, peak knee extension moment, but larger peak knee varus moment than the low collar shoes. Stiffer counter-stiffness shoes related to smaller ankle inversion at touchdown and total coronal RoM, but larger peak knee flexion and increased total ankle and knee sagittal RoM than the less stiff counter-stiffness. Furthermore, wearing stiffer counter-stiffness shoes increased forefoot GRF peak at high collar condition, while no significant differences between counter-stiffness at low collar condition. These results suggest that although higher collar height and/or stiffness heel counter used can reduce ankle motion in coronal plane, it would increase the motion and loading at knee joint, which is susceptible to knee injuries. These findings could be insightful for training and footwear development in basketball.